2018
DOI: 10.1080/24750573.2018.1480081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of depression, anxiety, alexithymia, attachment, social support and somatization in functional dyspepsia

Abstract: AIM: The psychiatric and psychosocial aetiology of Functional dyspepsia is not well known. In the present study, our aim is to determine the relative contributions of psychiatric predictorsi.e. depression, anxiety, somatization, alexithymiain relation with socio-psychological factors, specifically their personal characteristics (i.e. emotional attachment) and perceived social support, in distinguishing FD from organic dyspepsia and healthy samples. MATERIAL AND METHODS: An estimated 30 functional dyspepsia, 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(83 reference statements)
0
3
0
1
Order By: Relevance
“…The communications between the brain and gut through enteric neurohumoral systems played important roles in the pathogenesis of FD [24]. Some psychological factors, including depression, anxiety, somatization, alexithymia and sleep disorder, were extensively investigated to identify their contributions to FD [25][26][27]. Among those factors, depression and anxiety were most frequently explored and demonstrated to be significant psychological factors associated with FD [28].…”
Section: Discussionmentioning
confidence: 99%
“…The communications between the brain and gut through enteric neurohumoral systems played important roles in the pathogenesis of FD [24]. Some psychological factors, including depression, anxiety, somatization, alexithymia and sleep disorder, were extensively investigated to identify their contributions to FD [25][26][27]. Among those factors, depression and anxiety were most frequently explored and demonstrated to be significant psychological factors associated with FD [28].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate logistic regression questioning the independent predictor role of mucosal defects, pathological findings, drugs and comorbidities in anemic patients with premalignant gastric lesions and a negative history of CKD linked to H. pylori infection, as H. pylori-positive individuals with dyspeptic symptoms shared the same clinical characteristics as the uninfected group [18]. Functional dyspepsia may be aggravated by various psychosocial factors and psychiatric conditions [19], somatization, or depression [20]. Our study confirmed the decreased risk of anemia and significant clinical and histologic gastro-duodenal changes in patients with dyspeptic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the term MUPS is still widely used by primary health physicians and other medical disciplines (Lamahewa et al, 2019;Olde Hartman et al, 2017;van Westrienen et al, 2019;Ziadni et al, 2018) The coexistence and overlap between depression, anxiety, and alexithymia in patients with unexplained physical symptoms attending primary care facilities have been identified and discussed by psychosomatic specialists (Löwe et al, 2008). The high comorbidity rates across those three symptoms have been highlighted in recent literature tackling various pathologies such as unexplained dyspepsia or fibromyalgia (Kani et al, 2019;Melin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%